Results of socio-economic survey in coastal areas of Guyana (IICA GeorgetownGY, 1994)
Presents information on Guyana's economy and the agricultural sector, as well as the results of the survey in respect to the farm, land use, production, productivity and marketing of diverse crops, and agricultural services. Focuses on the population in the surveyed areas, social infrastructure and services, and income levels. Evaluates the level of poverty in the surveyed area.
DC